Regional cooperation in a changing global environment : success and failure of East Asia - Yamazawa, Ippei (UN New YorkUS, 1999)
Presents an overview of the experience of the East Asian developing economies in responding to the globalization challenge, and examines how regional cooperation helps them. Concludes with a series of prescriptions for actions needed at the national, regional and global levels to address some of the harmful effects of globalizaion and to enable economies to take advantage of the many opportunities it presents.